Pengaruh Fiscal Stress, Varians Anggaran Dan Perubahan Sisa Lebih Perhitungan Anggaran Terhadap Perubahan Anggaran Belanja Pada Pemerintah Daerah - Arief Kurniawan; Fefri Indra Arza (Universitas Negeri Padang, 2019)
The objective of this study is to determine the effect of fiscal stress, budget variances, and rebudgeting in time over budget calculation (SiLPA) to budget expenditure change on local government in West Sumatera. The sample of this study using the 19 districts/cities in West Sumatera period of 2013-2017. Sampling was done by using total sampling method. The type of data used is secondary data obtained from local regulation data on rebudgeting in revenue and expenditure (P-APBD), then data in local government financial report (LKPD). The analytical method used is panel regression analysis models were performed with Eviews10. Results of regression testing showed that only rebudgeting in SiLPA which effect positive and significant to budget expenditure change, while fiscal stress and both of budget variances (revenue variance and expenditure variance) does not significantly effect to budget expenditure change on local government (districts/cities) in West Sumatera period of 2013-2017.